2021
DOI: 10.1186/s12913-021-06414-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of China’s zero mark-up drug policy on drug cost of NCDs’ outpatients: an interrupted time series analysis

Abstract: Background China proposed the Zero Markup Drug Policy (ZMDP), which popularized in tertiary hospitals across the country in 2017, to control drug expenditures’ rapid growth further and reduce the public’s medical burden. This study aims to evaluate the impact of ZMDP on the drug cost of chronic disease outpatients in the tertiary hospital in Chongqing. Methods We collected and described the drug-cost data for outpatients with chronic diseases in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…We discarded 25 records that could not fulfill the selection criteria. Fifteen studies (including retrospective cohort studies, time series studies, and quasiexperimental studies) were eventually included (1)(2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Table 3 outlines the features of the selected studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…We discarded 25 records that could not fulfill the selection criteria. Fifteen studies (including retrospective cohort studies, time series studies, and quasiexperimental studies) were eventually included (1)(2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Table 3 outlines the features of the selected studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…One study showed that the number of medicines prescribed per patient and the use of antibiotics, intramuscular injections, and intravenous injections reduced, while the use of hormones increased (12). The total drug expenditure decreased by 14.4%, while the drug expenditure of outpatients with chronic diseases in tertiary hospitals was reduced due to the implementation of the ZPED (14,16).…”
Section: Drug Costmentioning
confidence: 99%
See 3 more Smart Citations